The Role of Satisfaction and Trust in Mediating the Relationship Between Payment Method and Vendor Loyalty (Study on Construction Company PT. Wijaya Karya) - I Gusti Agung Gede Usadhana AWATARA; Ni Luh Putu INDIANI; Ni Made WAHYUNI (PT Keberlanjutan Strategis Indonesia, 2026)
Loyalty is crucial for sustainable business relationships and long-term company success. In competitive business environments, companies must enhance loyalty by focusing on key factors. This research aims to examine how satisfaction and trust mediate the impact of payment on vendor loyalty at PT. Wijaya Karya. Using a quantitative method and questionnaire, the study targets 120 vendors who have contracts with PT. Wijaya Karya Infrastructure Division I. This research uses 5 Likert scales to measure variables when testing the validity and reliability of variables. This research was analyzed using PLS-based SEM. The research results show that (1) Payment has a positive and significant effect on satisfaction, (2) Payment has a positive and significant effect on trust, (3) Payment has a positive and significant effect on loyalty (4) Satisfaction has a positive and significant effect on loyalty (5) Trust positive and significant effect on loyalty (6) Payment has a significant effect on loyalty through satisfaction (7) Payment significantly influences loyalty through trust. Theoretically, this research develops a model linking payment, satisfaction, trust, and vendor loyalty, enhancing our understanding of vendor loyalty in business relationships. Practically, PT. Wijaya Karya should focus on improving payment, satisfaction, and trust to boost vendor loyalty. The study contributes to business relationship management literature and offers practical recommendations for PT. Wijaya Karya. Future research should consider additional factors like experience, relationship quality, and communication quality to further explore vendor loyalty.